Determination of Trace Amount of Iron with as-Triazine Containing Ferroin- Functional Group - Hossain, Md Musharraf; Islam, Md Anwarul; Begum, Shahida; Parvin, Maksuda (Dhaka University Journal of Science, 2019)
The as-triazines containing iron(II) methine chromophoric group; 3-(2-pyridyl)-5,6-diphenyl-as-triazine (PDT), and 3-(2- pyridyl)-5,6-bis(p-methoxyphenyl)-as-triazine (PBMPT) have been prepared from commercially available relatively cheaper reagents. The absorptiometric characteristics of the iron(II) complexes with PDT and PBMPT have been re-evaluated. The interference of copper ion on the determination of iron with these selective reagents and its masking has also been studied. The application of these spectrophotometric reagents for determination of iron in water samples based on the formation of extractable PDT-iron(II) and PBMPT-iron(II) complexes in chloroform medium has been described. Standard addition technique was used to verify the reliability of the method. Repeated determinations gave results with a very small standard deviation. Dhaka Univ. J. Sci. 67(2): 145-150, 2019 (July)